The Lacconectus Motschulsky of Hainan, China, with description of a new species (Coleoptera: Dytiscidae: Copelatinae) - Hájek, Jiří; Zhao, Shuang; Jia, Fenglong (Zootaxa, 2013)
Lacconectus brancuccii sp. nov. from Hainan Island, China, is described and illustrated. The new species belongs to the L. fulvescens species group and can be recognised based on the broader, poorly delimited pale basal markings on the elytra, but predominantly based on the characteristic shape of the median lobe of the aedeagus, which in lateral view is slightly narrowed subapically, then broadened to a rounded apex. Previous records from Hainan attributed to L. formosanus (Kamiya, 1938) are found to refer to L. maoyangensis Brancucci, 2003. Additional records of two further species endemic to Hainan, L. hainanensis Hendrich, 1998 and L. maoyangensis, are presented and their habitus are figured.